2009
DOI: 10.1002/lpor.200810064
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐fast nano‐optics

Abstract: Ultra-fast nano-optics is a comparatively young and rapidly growing field of research aiming at probing, manipulating and controlling ultrafast optical excitations on nanometer length scales. This ability to control light on nanometric length and femtosecond time scales opens up exciting possibilities for probing dynamic processes in nanostructures in real time and space. This article gives a brief introduction into the emerging research field of ultrafast nano-optics and discusses recent progress made in it. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 149 publications
0
53
0
Order By: Relevance
“…This tip geometry provides near-optimal excitation and collection properties for nano-Raman and nano-IR/FTIR hyperspectral imaging and also enables measurements such as white-light nano-ellipsometry/interferometric mapping of dielectic functions, nonlinear optical experiments that involve multiple optical frequencies (such as sum-frequency and secondharmonic generation), coherent anti-Stokes and stimulated Raman spectroscopy, as well as other ultrafast pump-probe investigations of local dynamics [82]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This tip geometry provides near-optimal excitation and collection properties for nano-Raman and nano-IR/FTIR hyperspectral imaging and also enables measurements such as white-light nano-ellipsometry/interferometric mapping of dielectic functions, nonlinear optical experiments that involve multiple optical frequencies (such as sum-frequency and secondharmonic generation), coherent anti-Stokes and stimulated Raman spectroscopy, as well as other ultrafast pump-probe investigations of local dynamics [82]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, graphene is the ultimate thin surface layer. This fact, together with the ability of tuning the value of the chemical potential by an external gate, makes this system particularly interesting, since the formation of this type of electromagnetic surface waves can by controlled externally.From the point of view of applications, surface plasmonpolaritons can be explored in plasmon sensors [14] and highresolution imaging [15], as well as for the miniaturization of photonics components [16][17][18]. In this Letter, we show that it is feasible to achieve a sharp resonance of the attenuation of an electromagnetic wave by transferring its energy into the excitation of surface plasmon-polaritons in graphene.…”
mentioning
confidence: 91%
“…Such intense electron emission was only seen when polarizing the incident pulses along the taper axis, clearly illustrating the polarization sensitivity of the field enhancement promoting electron generation. By comparing the electron flux from the tip apex to that from the shaft, we could estimate local field enhancement factors of about 10 for our gold tips [131]. Interferometric autocorrelation of the laser pulses detected via the electron signal [26] indicated that electron emission from the tip occurs on time scales shorter than our resolution of about 10 fs.…”
Section: Introductionmentioning
confidence: 99%